Diminution of the COD in Formation Waters Using Bacterial Stocks - Castro Echavez, Fernando Luis; Fernández Acosta, Nola María; Chávez Delgado, Magaly Jackelin (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Five groups bacteria were isolated and identified from liofilizated samples of contaminated soil. The identification of these bacteria included: Gram stain, oxygen tension and, biochemical tests. Individually and in consortium, the microorganisms isolated were used to conduct a treatability study on a laboratory scale as well as in a mesofílics aerobic reactors with load of 3 L, that have a useful volume of 1 L. The reactor cointaned 0,3 L of bacterial suspension and 0,7 L of water supplemented with a formation of mediated petroleum. Before and during the 6 days of experimentation were measured the pH, COD, total alkalinity, VSS and TSS of formation water were. The results considered were those collected from the second day of treatment, since it is then when the conditions in the reactors are more stable and the microorganisms are more adapted to medium provided. Those results indicated an efficient reduction of the COD, (between 62,4 and 89,8%), while using the different bacterial stocks properly characterized and the consortium., this finding showed the efficiency of the individual microorganisms and in groups to biodegrade complex organic matter present in the water formation used. We found that the bacterial consortium was more efficient in the reduction of the COD (89,8%), followed by Xanthomonas (84%) and Aeromonas (80,6%) genus.